Quality of Care of Adult Patients With Allergic Diseases in Urban, Rural, and Remote Primary Care Sites in the Philippines - Carol Stephanie C. Tan-Lim; Robbi Miguel G. Falcon; Jeremiah F. Feliciano; Michael B. Fong MD; Mark Anthony U. Javelosa; Leonila F. Dans; Iris Thiele C. Isip-Tan; Josephine T. Sanchez; Mia P. Rey; Antonio Miguel L. Dans (Journal of Primary Care & Community Health)
Introduction: This study determined the clinic prevalence and compared the quality of care of allergic diseases in urban, rural, and remote primary care sites. Methods: This was a retrospective review of electronic health records of all adult patients who consulted in the 3 sites from May 2019 to April 2022. Data of adult patients with allergic diseases was extracted from the 3 EHR systems operating across the participating sites using standardized Structured Query Language queries across the 3 systems. We computed the prevalence of allergic diseases among adults who consulted in primary care health facilities by dividing the number of patients diagnosed to have an allergic disease over the total number of adult patients who consulted within the 3-year study period. We compared the quality of care of patients across the 3 sites based on clinical practice guidelines using Chi-square test, Fisher’s exact test, or 1-way analysis of variance, as appropriate. Results: The prevalence of allergic disease among adults who consulted in primary care health facilities was 1.3% for the urban site, 2.2% for the rural site, and 2.1% for the remote site. The most common allergic disease was asthma (59.0%). First-line medications based on recommendations in clinical practice guidelines were prescribed more often in the urban site, including inhaled corticosteroids with long-acting beta-agonists for asthma patients ( P  < .001) and topical corticosteroids for atopic dermatitis ( P  < .001). In contrast, there was more frequent prescription of medications that were not recommended in clinical practice guidelines in the rural and remote sites. Conclusion: Health inequity was observed in this study, with results demonstrating that the rural and remote sites had greater allergic disease prevalence, greater underutilization of first-line medications, and more frequent overutilization of non-essential medications.